On the likely extent of falls in Irish house prices - Morgan Kelly (University College Dublin, UCD School of Economics, 2007)
Looking at house price cycles across the OECD since 1970, we find a strong relationship between the size of the initial rise in price and its subsequent fall. Were this relationship to hold for Ireland, it would predict falls of real house prices of 40 to 60 per cent over a period of 8 to 9 years. House price falls tend not to have serious macroeconomic consequences, but the unusually large size of the Irish house building industry suggest that any significant house price fall that does occur could impose a difficult adjustment on the economy.
Keywords: 330; Immobilienpreis; Konjunktur; Volatilität; Irland